054 Disability improvement is observed in each functional system in alemtuzumab-treated patients with active RRMS: results from CARE-MS II extension. Issue 6 (24th May 2018) - Macdonell, Richard AL; Aburashed, Rany A; Alroughani, Raed; Dive, Dominique; Izquierdo, Guillermo; Kim, Ho-Jin; Lycke, Jan; Pozzilli, Carlo; Sharrack, Basil; Vermersch, Patrick; Wiendl, Heinz; Lysandropoulos, Andreas; et al.
Abstract : Introduction: In CARE-MS II (NCT00548405 ), alemtuzumab (12 mg/day, baseline: 5 days; 12 months later: 3 days) significantly improved clinical/MRI outcomes versus subcutaneous interferon beta-1a over 2 years in relapsing-remitting MS patients with inadequate response to prior therapy; significantly greater percentage of alemtuzumab-treated patients achieved 6 month confirmed disability improvement (CDI). Efficacy remained durable in a 4 year extension (NCT00930553 ). Here we assess alemtuzumab efficacy on disability at the level of functional systems (FS) scores of the Expanded Disability Status Scale (EDSS) over 6 years. Methods: EDSS and individual FS scores were recorded at baseline and quarterly; CDI (≥1.0 point EDSS decrease confirmed over 6 months) was assessed in patients with baseline EDSS score ≥2.0. Results: Of the 393 patients who entered the extension, 338 (86%) remained on study through Year 6; 50% received neither alemtuzumab retreatment nor other disease-modifying therapy after the initial 2 courses. Through Years 3–6, 76%–80% of patients showed stable (≤0.5 point change) or improved (≥1.0 point decrease) EDSS scores versus core study mean (SD) baseline score of 2.7 (1.2);≥75% were stable/improved in each FS. Through Year 6, 43% achieved 6 month CDI and 96% of patients with CDI had an EDSS score <4. 71% of patients with CDI achieved improvements in >1 FS. Improvements were observed in each FS, most frequently occurring in the sensory (48%), pyramidal (44%), and cerebellar (44%) systems; 21%–25% showed improvements in the brainstem, cerebral, visual, and bowel/bladder FS. Conclusion: Most (86%) CARE-MS II patients who entered the extension remained on the study through Year 6;≥75% of alemtuzumab-treated patients had improved/stable scores across all FS over 6 years. Improvements were seen for each FS in patients with 6 month CDI, with 71% showing improvements in >1 FS, indicating a broad treatment effect with alemtuzumab on multiple aspects of disability improvements. Study support: Sanofi and Bayer HealthCare Pharmaceuticals.